МОДЕЛЬ ВИКОРИСТАННЯ СИСТЕМИ ПІДТРИМКИ E-LEARNING ДЛЯ РОЗВИТКУ ІКТ-КОМПЕТЕНТНОСТЕЙ ПРАЦІВНИКІВ ЦЕНТРІВ ДИСТАНЦІЙНОЇ ОСВІТИ УНІВЕРСИТЕТІВ - Zabolotskii, Anton Yu (Information technologies and learning tools, 2017)
The article presents the e-learning support system’s construction for the university. It is provided the model of using the e-learning support system as a tool to increase ICT competence of employees of the distance education centres of universities. There are formulated main tasks that the e-learning support system should solve. It has been carried out analysis of the theory of knowledge, philosophy and psychology on the subject nature of human activity, the activity approach to the development of the person, didactic positions, the theory of the step-by-step formation of mental actions, didactic ideas of the problem approach to learning process. It was stated that one of the key problems of the informatization of society is a problem of a human interaction with various information systems. This problem is especially acute in education domain, where the role of the teacher as the most important source of knowledge was considered traditionally unconditional. The above mentioned challenges need to seek a new model of the educational process, to redefine the functions of its participants. В статье представлено формирование системы поддержки e-learning в университете. Анализ модели использования системы поддержки е-learning как средства развития ИКТ-компетентностей работников центров дистанционного образования университетов. Сформулированы основные задачи, что должна решать система поддержки e-learning. Проведенный анализ положения теории познания, философии и психологии о предметный характер человеческой деятельности, деятельностный подход к развитию личности, дидактические положения, теория поэтапного формирования умственных действий, дидактические идеи проблемного подхода к процессу обучения. Одной из ключевых проблем современности информатизации общества является проблема взаимодействия человека с различными информационными системами. Особенно остро эта проблема стоит в сфере образования, где традиционно роль преподавателя как важнейшего источника знаний остается неоспоримой. Все это заставляет находить новую модель образовательного процесса, заново определять функции его участников. У статті представлено формування системи підтримки e-learning в університеті. Подано аналіз моделі використання системи підтримки е-learning як засобу розвитку ІКТ-компетентностей працівників центрів дистанційної освіти університетів. Сформульовані основні завдання, які повинна вирішувати система підтримки e-learning. Проведено аналіз положення теорії пізнання, філософії й психології про предметний характер людської діяльності, діяльнісний підхід до розвитку особистості, загально-дидактичні положення, теорія поетапного формування розумових дій, дидактичні ідеї проблемного підходу до процесу навчання. Однією з ключових проблем сучасної доби інформатизації суспільства є проблема взаємодії людини з різноманітними інформаційними системами. Особливо гострою є проблема у сфері освіти, де традиційно роль викладача, як найважливішого джерела знань, вважалася беззаперечною. Усе це примушує відшукувати нову модель освітнього процесу, по-новому визначати функції його учасників.